Prioritization of PLEC and GRINA as Osteoarthritis Risk Genes Through the Identification and Characterization of Novel Methylation Quantitative Trait Loci. Issue 8 (27th June 2019) - Rice, Sarah J.; Tselepi, Maria; Sorial, Antony K.; Aubourg, Guillaume; Shepherd, Colin; Almarza, David; Skelton, Andrew J.; Pangou, Ioanna; Deehan, David; Reynard, Louise N.; Loughlin, John
Abstract : Objective: To identify methylation quantitative trait loci (mQTLs) correlating with osteoarthritis (OA) risk alleles and to undertake mechanistic characterization as a means of target gene prioritization. Methods: We used genome‐wide genotyping and cartilage DNA methylation array data in a discovery screen of novel OA risk loci. This was followed by methylation, gene expression analysis, and genotyping studies in additional cartilage samples, accompanied by in silico analyses. Results: We identified 4 novel OA mQTLs. The most significant mQTL contained 9 CpG sites where methylation correlated with OA risk genotype, with 5 of the CpG sites having P values <1 × 10 −10 . The 9 CpG sites reside in an interval of only 7.7 kb within the PLEC gene and form 2 distinct clusters. We were able to prioritize PLEC and the adjacent gene GRINA as independent targets of the OA risk. We identified PLEC and GRINA expression QTLs operating in cartilage, as well as methylation‐expression QTLs operating on the 2 genes. GRINA and PLEC also demonstrated differential expression between OA hip and non‐OA hip cartilage. Conclusion: PLEC encodes plectin, a cytoskeletal protein that maintains tissue integrity by regulating intracellular signaling in response to mechanical stimuli. GRINA encodes the ionotropic glutamate receptor TMBIM3 (transmembrane BAX inhibitor 1 motif–containing protein family member 3), which regulates cell survival. Based on our results, we hypothesize that in a joint predisposed to OA, expression of these genes alters in order to combat aberrant biomechanics, and that this is epigenetically regulated. However, carriage of the OA risk–conferring allele at this locus hinders this response and contributes to disease development.